1,25-D3 attenuates cerebral ischemia injury by regulating mitochondrial metabolism via the AMPK/AKT/GSK3β pathway - Li, Yutian; Li, Xiangling; Xu, Shuangli; Zhao, Yingzhe; Pang, Meng; Zhang, Xiaojun; Wang, Xuejian; Wang, Yanqiang (Frontiers in Aging Neuroscience, 2022)
The brain injury caused by cerebral ischemia-reperfusion is related to mitochondrial damage. Maintaining the normal function of mitochondria, promoting angiogenesis, protecting neuronal cells, and resisting oxidative stress are the keys to functional recovery after acute ischemic stroke. In this study, we established a middle cerebral artery occlusion (MCAO) model and investigated the effects of 1α,25-dihydroxyvitamin D3 (VitD or 1,25-D3) on mitochondrial function via the adenosine 5'-monophosphate-activated protein kinase (AMPK)/protein kinase B (AKT)/glycogen synthase kinase-3β (GSK-3β) signaling pathway in rats with cerebral ischemia-reperfusion injury. The neurological function and infarct size were measured in each group. Hematoxylin-eosin, neuronal nucleus, and Nissl staining procedures were conducted to observe the morphology and number of the cerebral cortical neurons. Western blotting was then used to analyze p-AMPK, vitamin D receptor (VDR), p-GSK-3β, p-AKT, P53, cytochrome C (CytC), TGF-β, and vascular endothelial growth factor (VEGF) in mitochondria. Immunofluorescence staining was used to observe the expression of CytC and caspase-3. Succinate dehydrogenase, ATPase, reactive oxygen species, and malondialdehyde were detected by kits. RT-qPCR was used to analyze TGF-β, VEGF, P53, and CytC mRNA. The results revealed that the cerebral infarct volume, neurological function score, apoptotic protein P53, CytC, caspase-3, reactive oxygen species, and malondialdehyde were significantly increased in MCAO rats. 1,25-D3 reduced the infarct size and neurological function score, activated VDR, upregulated TGF-β, p-AMPK, p-AKT, p-GSK-3β, VEGF, ATP, and succinate dehydrogenase, and downregulated P53, CytC, caspase-3, reactive oxygen species, and malondialdehyde. As an antagonist of VDRs, pyridoxal-5-phosphate could partially block the neuroprotective effect of 1,25-D3. In conclusion, 1,25-D3 activated AMPK/AKT/GSK-3β signaling and VDRs, inhibited P53, CytC, and caspase-3, increased TGF-β and VEGF, regulated mitochondrial metabolism, reduced neuronal apoptosis, promoted vascular growth, and exerted neuroprotective effects. These findings suggest that this signaling pathway may be an effective target for the treatment of ischemic stroke.